PARAMETRIC SYNTESIS OF PANEL ANTENNAS - Ільницький, Л.; Щербина, О.; Михайлішен, Д. (Science-based technologies, 2011)
The relationship between field radiation of patch antenna and its design parameters is considered. The formulas, which enables to calculate for two or four element patch antenna the length of radiators and their position over the flat screen are obtained.